Predicting Airflow and Temperature Pattern Inside A Refrigerator Through CFD - Haque, Muhammad E.; R. A., Bakar; Gan, Leong Ming; Shakaib, M. (Asian Research Publishing Network (ARPN), 2016)
An optimized Computerized Fluid Dynamics (CFD) model for frost-free refrigerators is reported A steady-state simulation model was devised and its predictions for temperature and air flow were compared with experimental data. The conservation equations of energy, mass and momentum are solved by using Finite Volume Method in an environment of three dimensional unstructured meshes. Experiments were conducted on a no-frost domestic refrigerator to compare and validate the results of the CFD model. For the refrigerator under analysis it was found that results from the CFD model and experiment are qualitatively similar even though there are certain discrepancies due to some insufficient information available for the numerical model.